2018
DOI: 10.3389/fpsyg.2018.01013
|View full text |Cite
|
Sign up to set email alerts
|

Weight Fluctuation and Diet Concern Negatively Affect Food-Related Life Satisfaction in Chilean Male and Female Adolescents

Abstract: Problematic eating behaviors and obesity are frequent problems encountered during adolescence that may potentially result in psychological, social and physical consequences that may interfere with adolescent development and well-being. The present study evaluates the relationship between satisfaction with food-related life and satisfaction with family life, and their relationship with life satisfaction in male and female adolescents. We explored the relationships between both subscales of the Revised Restraint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 88 publications
(148 reference statements)
3
15
0
Order By: Relevance
“…Finally, we did not assess family diet quality or food-related parenting practices used by parents, which may differ according to the level of the parents’ work-life balance [ 47 , 48 , 49 , 50 , 51 ]. Future studies should incorporate these variables, since they may affect the nutritional status and well-being in adolescents [ 9 , 13 , 17 , 58 , 60 , 67 , 68 ]. Therefore, in addition to the adolescents’ age, gender and socioeconomic status, future studies may also control for adolescents’ body mass index.…”
Section: Limitations and Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, we did not assess family diet quality or food-related parenting practices used by parents, which may differ according to the level of the parents’ work-life balance [ 47 , 48 , 49 , 50 , 51 ]. Future studies should incorporate these variables, since they may affect the nutritional status and well-being in adolescents [ 9 , 13 , 17 , 58 , 60 , 67 , 68 ]. Therefore, in addition to the adolescents’ age, gender and socioeconomic status, future studies may also control for adolescents’ body mass index.…”
Section: Limitations and Conclusionmentioning
confidence: 99%
“…Bottom-up theoretical approaches to life satisfaction imply that life satisfaction depends on the level of satisfaction a person feels in regard to different life domains [ 9 ]. Recent studies based on this approach have established that satisfaction within the food and family domains are positively related to overall life satisfaction in adolescents [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Whereas satisfaction with food-related life is defined as a person’s overall assessment of their food and eating habits [ 18 ], satisfaction with family life is defined as a conscious cognitive judgment of one’s family life [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have reported that dietary restraint is related to lower levels of life satisfaction in adolescents and emerging adults 20 while others have reported no association between dietary restraint and life satisfaction 21 . Similarly, dietary restraint has been also associated with lower levels of satisfaction in the food domain in adolescents and university students 20,22,23 . In addition, researchers have suggested that individuals with eating disorders are impaired in other important domains of their lives, such as in social relationships 22 .…”
Section: Latent Class Analysis Of Dietary Restraint In Mother-adolescent Dyadsmentioning
confidence: 97%
“…Although girls and female adolescents are more prone to dietary restraint 16 and usually have higher values of restrained eating than boys 7 , the relationship between higher BMI and dietary restraint exists in adolescents of both genders 7 . Furthermore, recent studies have suggested that "the gap between male and female individuals in dietary restraint may be narrowing" 22,23 .…”
Section: Latent Class Analysis Of Dietary Restraint In Mother-adolescent Dyadsmentioning
confidence: 99%